2011
DOI: 10.1625/jcam.8.1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of a Water-Soluble Extract from Culture Medium of Ganoderma lucidum (Rei-shi) Mycelia on Postprandial Blood Glucose Elevation in Type 2 Diabetic Mice and Additional Effect with .ALPHA.-Glucosidase Inhibitors

Abstract: The water-soluble extract of Ganoderma lucidum mycelia (WER) is prepared from a solid medium composed of bagasse and rice bran overgrown with Ganoderma lucidum mycelia. Recently, we reported that WER shows a blood glucose-lowering effect in maltose-loaded non-diabetic mice. Here, we investigated the efficacy of WER in type 2 diabetic state using KK-A y mice. Moreover, the food-drug interactions of WER with α-glucosidase inhibitors, voglibose or acarbose were examined using both in vitro and in vivo experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…The observed melting point value (133–135°C) was also comparable with the reported melting point value of β-sitosterol (i.e. 135–136°C) [27]. Therefore, based on the observed spectral and melting point data, compound CA1 is most likely β-sitosterol.…”
Section: Resultssupporting
confidence: 83%
“…The observed melting point value (133–135°C) was also comparable with the reported melting point value of β-sitosterol (i.e. 135–136°C) [27]. Therefore, based on the observed spectral and melting point data, compound CA1 is most likely β-sitosterol.…”
Section: Resultssupporting
confidence: 83%
“…However, the DCM and water extract had no appreciable bioactivities against the growth of M. smegmatis . Traditional healers use water as a solvent to extract phytochemicals from plant materials when treating different kinds of illness Sasidharan et al, [44]. In most phytochemical studies, the water extracts of different plants are reported to have no bioactivities [45].…”
Section: Discussionmentioning
confidence: 99%
“…After drying, a total of 27.32 g of dry extract was collected. The extract was stored in tightly closed bottle container in a refrigerator at −20 °C until used [11]. …”
Section: Methodsmentioning
confidence: 99%